2018
DOI: 10.1103/physrevb.98.184403
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical structure factor of the triangular antiferromagnet: Schwinger boson theory beyond mean field

Abstract: We compute the zero temperature dynamical structure factor S(q, ω) of the triangular lattice Heisenberg model (TLHM) using a Schwinger boson approach that includes the Gaussian fluctuations (1/N corrections) of the saddle point solution. While the ground state of this model exhibits a well-known 120 • magnetic ordering, experimental observations have revealed a strong quantum character of the excitation spectrum. We conjecture that this phenomenon arises from the proximity of the ground state of the TLHM to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 85 publications
4
69
0
Order By: Relevance
“…In Ref. 37 we demonstrated that, even for S = 1/2 (quantum limit), the spin velocities of these poles basically coincide with the spin-wave velocities obtained from LSWT plus 1/S corrections. 35,38,39 In this work we demonstrate these poles coincide over the full Brillouin zone with the ones obtained from LSWT in the S → ∞ limit.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…In Ref. 37 we demonstrated that, even for S = 1/2 (quantum limit), the spin velocities of these poles basically coincide with the spin-wave velocities obtained from LSWT plus 1/S corrections. 35,38,39 In this work we demonstrate these poles coincide over the full Brillouin zone with the ones obtained from LSWT in the S → ∞ limit.…”
Section: Introductionsupporting
confidence: 63%
“…The After introducing the Hubbard-Stratonovich (HS) transformations that decouple the AA and BB terms, 37 the partition function becomes…”
Section: Saddle Point Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…Already the first theoretical studies of spin dynamics exposed salient deviations from non-interacting magnon scenario of linear spin-wave theory. Not only the spin waves are renormalized, sometimes changing their shape to produce roton minima around the M -points [84][85][86], but also the spectrum is washed out into a broad continuum at energies ω > J 1 [86][87][88][89]. These findings were initially interpreted as signatures of spinon excitationsan idea inspired by the work on square-lattice Heisenberg antiferromagnets.…”
Section: B Hexagonal Perovskites and Magnetic Excitationsmentioning
confidence: 99%
“…However, going beyond the mean-field approximation is rather difficult within the Schwinger boson approach. [27][28][29][30] Another analytical approach to quantum ferromagnets is based on the decoupling of the equations of motion for the Green functions of the spins. [31][32][33] Of course, the physical properties of quantum ferromagnets can be obtained with high accuracy numerically using Monte Carlo simulations.…”
Section: Introductionmentioning
confidence: 99%